2012
DOI: 10.1017/s0317167100013196
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis Fatigue is Associated with Reduced Psychomotor Vigilance

Abstract: Fatigue is a common and disabling symptom in those who suffer from multiple sclerosis (MS). Studies indicate that more than 75% of MS patients suffer from fatigue. 1-3 Two-thirds of MS patients rank fatigue as one of their three most debilitating symptoms. 1 Multiple sclerosis fatigue is particularly aggravated by heat and can significantly impair physical activity. 1 It is one of the main causes of work absenteeism in individuals with MS. 4 Yet fatigue is a lay term that remains subjectively defined and asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
2
8
0
1
Order By: Relevance
“…Previous studies demonstrated that MS patients with fatigue present a larger vigilance decrement than healthy controls ( 2 , 16 ). Moreover, several studies found correlations between fatigue and vigilance decrement in MS patients ( 3 , 5 , 17 ). Therefore, vigilance tasks appear to be well suited to measure fatigue in MS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that MS patients with fatigue present a larger vigilance decrement than healthy controls ( 2 , 16 ). Moreover, several studies found correlations between fatigue and vigilance decrement in MS patients ( 3 , 5 , 17 ). Therefore, vigilance tasks appear to be well suited to measure fatigue in MS.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the relation between fatigue and cognitive performance in multiple sclerosis (MS) patients found evidence for a relation between fatigue and vigilance ( 1 – 5 ). Vigilance tasks require an individual to sustain attention during a repetitive monotonous task over a prolonged period of time ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…These remarks concern only the direct application of relatively short tests for the objectification of fatigue as well as test batteries which provide frequent changes between short tests. Another strategy in the measurement of fatigue analyzes the effect on the test process, the so-called time-on task effect, and this could actually represent a central variable [33]. Fot the PASAT several research groups have shown (although not always reproducible) that the MS patients with fatigue show a stronger performance decline compared to non-fatigue groups at the end of the test [34].…”
Section: Measurement Of Fatigue Using Neuropsychological Test Proceduresmentioning
confidence: 99%
“…Alle diese Ausführungen gelten nur für die unmittelbare Anwendung von relativ kurzen Tests zur Objektivierung von Fatigue und für Testbatterien, welche einen häufigen Wechsel zwischen kurzen Tests vorsehen. Eine andere Strategie in der Messung der Fatigue analysiert dagegen deren Auswirkung auf den Testverlauf, d. h. den sogenannten Time-on-Task-Effekt, und dieser könnte tatsächlich eine zentrale Variable darstellen [33]. Für den PASAT konnten mehrere Forschergruppen, wenn auch nicht immer replizierbar, zeigen, dass MS-Patienten mit Fatigue gegen Ende des Tests einen stärkeren Leistungseinbruch zeigen als Vergleichsgruppen ohne Fatigue [34] [35] (unter Ausschluss der somatischen Items), die Hospital Anxiety and Depression Scale (HADS) [36], den Pittsburgh Schlafqualitätsindex (PSQI) [37] und die Epworth-Schläfrigkeitsskala (ESS) [38] an.…”
Section: Messung Von Fatigue Mit Neuropsychologischen Testverfahrenunclassified